2017
DOI: 10.15766/mep_2374-8265.10570
|View full text |Cite
|
Sign up to set email alerts
|

A Video-Based Introductory EEG Curriculum for Neurology Residents and Other EEG Learners

Abstract: Introduction: It is difficult to provide standardized formal education in EEG because of time limitations and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…30 Two-thirds of respondents (10/15) reported having watched all the videos and 87% (13/15) at least half of them. 30 Videos provide the possibility of adding analytical viewing patterns to self-reports. This allows the educators to analyze whether learners persisted or stopped watching videos, providing the means of updating the curriculum and closing the loop on educational deficits through in-person sessions.…”
Section: Current Implementations In Neurologymentioning
confidence: 99%
See 2 more Smart Citations
“…30 Two-thirds of respondents (10/15) reported having watched all the videos and 87% (13/15) at least half of them. 30 Videos provide the possibility of adding analytical viewing patterns to self-reports. This allows the educators to analyze whether learners persisted or stopped watching videos, providing the means of updating the curriculum and closing the loop on educational deficits through in-person sessions.…”
Section: Current Implementations In Neurologymentioning
confidence: 99%
“…Additionally, this approach has been used to implement an evidence‐based “think aloud” approach to clinical reasoning instruction, which can be a solution to time and resource constraints and aligns well with the pedagogical trend of standardized patient instruction . Concerning the latter, a set of 10 electroencephalography (EEG) teaching videos (based on concepts outlined in the Accreditation Council for Graduate Medical Education Neurology Milestones) proved to be a useful resource in complementing existing curricula at the resident level . Two‐thirds of respondents (10/15) reported having watched all the videos and 87% (13/15) at least half of them .…”
Section: Current Implementations In Neurologymentioning
confidence: 99%
See 1 more Smart Citation
“…38,39,41,48,52,53,56 Others suggested that the FC method was selected to improve didactic instruction, motivate or engage learners, promote active learning, or prepare for more advanced levels of content material. [38][39][40][41][42]44,46,47,49,54 Residency programs adopted the FC method in 1 of 3 ways. Most commonly, authors described ''occasional'' use of the FC for a single lesson, usually to emphasize an important topic such as quality improvement, 39,43 resident-as-teacher skills, 40 using clinical guidelines, 51 echocardiography or FIGURE PRISMA Diagram Illustrating Selection and Review Process of Articles Related to Flipped Classroom in Graduate Medical Education electro-encephalograph interpretation, 47,54,57 or pediatric advanced life-support.…”
Section: Education Contentmentioning
confidence: 99%
“…[38][39][40][41][42]44,46,47,49,54 Residency programs adopted the FC method in 1 of 3 ways. Most commonly, authors described ''occasional'' use of the FC for a single lesson, usually to emphasize an important topic such as quality improvement, 39,43 resident-as-teacher skills, 40 using clinical guidelines, 51 echocardiography or FIGURE PRISMA Diagram Illustrating Selection and Review Process of Articles Related to Flipped Classroom in Graduate Medical Education electro-encephalograph interpretation, 47,54,57 or pediatric advanced life-support. 52 Other programs have replaced their entire didactic curriculum with FC sessions.…”
Section: Education Contentmentioning
confidence: 99%